Effect of multidisciplinary team care on patient survival in chronic hepatitis B or C hepatocellular carcinoma - Tseng, Yu-Chen; Kung, Pei-Tseng; Peng, Cheng-Yuan; Chou, Wen-Yu; Tsai, Wen-Chen (Frontiers in Oncology, 2023)
Introduction: Multidisciplinary team care coordinates with medical teams to improve the quality of cancer care. This study explored multidisciplinary team care in hepatitis B or hepatitis C virus-related hepatocellular carcinoma patients from the time of diagnosis to the first-time treatment interval and investigated treatment outcomes and prognosis. Methods: This retrospective cohort study included data from a nationwide population from 2007 to 2016. Data were collected from the Taiwan Cancer Registry Database , linked to the Taiwan National Health Insurance Research Database. Propensity score matching was applied at a ratio of 1:2 to reduce the selection bias. A multiple regression model with generalized estimating equations was used to analyze whether multidisciplinary team care affected the diagnosis-to-treatment interval. The stratified Cox proportional hazards model examined whether involvement in multidisciplinary team care influenced survival status.Results: A total of 10,928 and 21,856 patients with hepatocellular carcinoma received multidisciplinary and non-multidisciplinary care, respectively. Participants with multidisciplinary care had a longer diagnosis-to-treatment interval but a lower risk of cumulative cancer death (HR=0.88, 95% CI:0.84-0.92). In patients with intermediate-to advanced-stage hepatocellular carcinoma, multidisciplinary team care has obvious benefits for improving survival.Patients with hepatocellular carcinoma who participated in multidisciplinary team care had a longer diagnosis-to-treatment interval but a lower risk of cancer death.Patients with intermediate-to advanced-stage hepatocellular carcinoma who received multidisciplinary team care significantly benefited from this outcome. Hospitals should provide HCC patients with multidisciplinary team care to improve cancer care.